The Path to Inclusive Growth in Nigeria: Are People with Disabilities Carried Along? - Okon, Emmanuel O. (American Economic & Social Review, 2018)
The growing disconnect between the improving macro-economic indicators and the growing descent into poverty of over 170 million Nigerians is clearly anindicative of the fact that economic growth in Nigeria is non-inclusive as the country may have only attained what is known as growth without development. Using a purely descriptive and analytical methodology, this paper shows that inclusive growth is the growth that generates employment opportunities and reduces the depth and severity of the incidence of poverty. However, people with disability have in many cases been denied of job opportunities in Nigeria. This paper argues that the country cannot have inclusive growth unless disability is made an integral part of her growth. Considering that the economic inclusion of people with disabilities is a cross-cutting issue, successful results require complementary activities in multiple sectors. However, inclusion of people with disabilities in work/employment can lead to greater economic self-sufficiency. Though it should not be promoted as the only option for economic inclusion, self-employment can be a good alternative, especially in a country like Nigeria where there is a general dearth of opportunities for formal sector jobs. In that regard, this paper suggests that microfinance institutions should extend credit and other financial services for self-employment of people with disabilities. Better still, specialized microfinance should be established for people with disabilities to provide supporting or complementary services.